2021
DOI: 10.48550/arxiv.2110.08298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Euclidean Contractivity of Recurrent Neural Networks

Abstract: Critical questions in neuroscience and machine learning can be addressed by establishing strong stability, robustness, entrainment, and computational efficiency properties of neural network models. The usefulness of such strong properties motivates the development of a comprehensive contractivity theory for neural networks.This paper makes two sets of contributions. First, we develop novel general results on non-Euclidean matrix measures and nonsmooth contraction theory. Regarding 1/ ∞ matrix measures, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In summary, we have shown that the solution of ( 8) is equal to x(t) = q − c lin t for all t ∈ [0, t c ] and is equal to d at time t c . Therefore from (9) and being x(t c ) = q − c lin t c , for all time t > t c we have x(t) = q − c lin t c e −cexp(t−tc) . Specifically, x(t) > 0 for all t > t c , thus it can never be the case x(t) < −d.…”
Section: Linear-exponential Decay Of Globally-weakly and Locally-stro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have shown that the solution of ( 8) is equal to x(t) = q − c lin t for all t ∈ [0, t c ] and is equal to d at time t c . Therefore from (9) and being x(t c ) = q − c lin t c , for all time t > t c we have x(t) = q − c lin t c e −cexp(t−tc) . Specifically, x(t) > 0 for all t > t c , thus it can never be the case x(t) < −d.…”
Section: Linear-exponential Decay Of Globally-weakly and Locally-stro...mentioning
confidence: 99%
“…In [9,Theorem 16] condition ( 5) is generalized for locally Lipschitz function, for which, by Rademacher's theorem, the Jacobian exists almost everywhere (a.e.) in C. Specifically, if f is locally Lipschitz, then f is infinitesimally contracting on C if condition (5) holds a.e.…”
Section: B Contraction Theory For Dynamical Systemsmentioning
confidence: 99%